Mentorship in undergraduate studies – building block for postgraduate success - Sindi Msimango (Journal of Student Affairs in Africa)
The need to improve access and throughput in higher education programmes in SA universities, especially in relation to the improvement of postgraduate and high-quality South African postgraduate publications continues to be a policy concern.  The problematic is as evident from the current higher education statistics and has been given attention through studies on entry requirements, and enrolment numbers. This paper is an inquiry into the undergraduate student experiences and how they contribute to professional identity formation and the progression to postgraduate study. The argument we explore is that experiences outside of the lecture room contribute to access and progression from under- to postgraduate studies. This is a mixed methods study of postgraduate students from various faculties in a Research-Intensive University and a Comprehensive University in South Africa. The main finding is that autonomy and agency contribute to professional identity formation and may be directly associated with postgraduate output. This is seen as important since identity is formed in social settings and social interactions and also through an individual’s own influence. Autonomy and autonomous actions can be used as a catalyst during undergraduate studies to help students access postgraduate studies.